Tissue-specific analysis of RVA RNA levels in extraintestinal tissues. - Sergei A. Raev (15350287) (2025)
Six-day-old germ-free pigs were orally inoculated with 1 × 106 FFU of rotavirus. At the post inoculation times indicated, animals were euthanized and tissues (lungs, salivary glands, liver, blood and spleen) were collected. (A) Levels of RVA RNA in extraintestinal tissues across dpi 1–4. (B) RT-qPCR RVA RNA detection frequency in extraintestinal tissues across dpi 1–4. (C) ISH RT-qPCR RVA RNA detection frequency in extraintestinal tissues across dpi 1–4 and (D) at time points when significant differences were observed. Statistical analysis for RVA RNA detection frequency was performed by using Fisher’s exact test. Significant differences (*p < 0.05) are indicated. (TIF)